Kajian Ekspresif Kepengarangan H.D Bastaman dalam Kumpulan Cerpen Sunda Nganjang ka Pagéto - Fauzi, Rusdi Fauzi; Koswara, Dedi; Haerudin, Dingding (Prodi Pendidikan Bahasa dan Sastra Daerah, 2024)
Abstract: This research is corcerned with the curiosity of how and in what way the author is able to produce a work that is satisfactory for the reader. The story of past events by a human being is called experience, through certain experiences we can take benefits for the present and the future. Literary works are popular because there is a creator, the author. The author as a social being cannot be separated from the surrounding social situation because a literary work is a copyright that expresses feelings. Honestly, the author embodies all the tastes inherent in a literary work, so the author as the creator of a particular work experiences a creative process. The theory used in this research is M.H.Abrams theory wich states that the center of the expressive desire and creative process of a work is the author. The source of data used is the short story collection book Nganjang ka Pagéto by H.D Bastaman. the methods and techniques used in this research are descriptive methods, literature review techniques, and documentation studies, while analyzing them using qualitative research.The instruments used are divided into two, namely data collection instrument and data processing instrument. The result of this research is a collection of short story books written by H.D Bastaman included as a work which has a great value, because many of them ride on psychological value, life, and socialist society. From the research results also we know that a lot of aspects affect the results of literary works trough self-authorship and surroundings. Keywords: expressive; psycological; short story.